The humanities facing the domain of technological reason and the crisis of the great stories - Hopenhayn, Martín (1993)
Today it seems incontestable that modernization in Latin America aspires to renew its impetus, and there is no one who gathers enough strength to oppose collective projects with real capacity for convocation. A new secularizing crusade imposes a code of universalist pretensions. Instrumental rationality updated, accelerated privatization, opening of the markets and a race against time to modernize the modernizable and manage the non-modernizable with its most colorful manifestations.